2019
DOI: 10.1039/c9cc04411f
|View full text |Cite
|
Sign up to set email alerts
|

Development of a unique reversible fluorescent probe for tracking endogenous sulfur dioxide and formaldehyde fluctuation in vivo

Abstract: A FRET-based reversible fluorescent probe for sensing SO2 and FA was designed. The probe was first used for imaging endogenous SO2 and FA in vitro and in vivo. Moreover, we first found that the interaction of SO2 and FA can reduce the cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…The marked emission changes (reduction and enhancement in the red and green channel, respectively) are in agreement with the isomerization of Ly-NT-SP to the merocyanine form Ly-NT-MR and subsequent reaction with lysosome SO 2 . For the control experiment, FA (formaldehyde), which is known as an inhibitor of bisulfite, was used for SO 2 imaging during heat shock …”
Section: Resultsmentioning
confidence: 99%
“…The marked emission changes (reduction and enhancement in the red and green channel, respectively) are in agreement with the isomerization of Ly-NT-SP to the merocyanine form Ly-NT-MR and subsequent reaction with lysosome SO 2 . For the control experiment, FA (formaldehyde), which is known as an inhibitor of bisulfite, was used for SO 2 imaging during heat shock …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies have shown that the concentration and metabolic abnormalities of active sulfur-containing molecules are closely related to a variety of diseases. For example, biothiol and hydrogen sulfide are closely related to cardiovascular diseases. The endogenous sulfur dioxide concentration is closely related to the occurrence and development of cancer. Studying their metabolic pathways is conducive to effective intervention to prevent the occurrence and development of related major diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the interconnected biological roles between SO 2 and FA, Lin et al creatively developed the first reversible probe 98 for sensing SO 2 and FA based on the Michael addition reaction and the reaction between nucleophilic bisulfite with electrophilic FA. 119 As shown in Fig. 19, the carbazolebenzopyrylium p-conjugated system was interfered by SO 2 via the Michael addition, resulting in a hypsochromic shift of fluorescence emission (from 645 nm to 540 nm).…”
Section: Miscellaneous Approachesmentioning
confidence: 95%